Hypoxia facilitates cancer associated cell marker expression in stem cells - Xu, L.; Xiao, H.; Xu, M.; Yi, L.; Liang, H. (Cellular and Molecular Biology, 2011)
How normal body cells differentiate to cancer cells is not clear. The present study aimed to investigate the mechanism by which hypoxia drives the expression of cancer associated cell markers in stem cells. In this study, mouse bone marrow mononuclear cells were prepared and cultured under hypoxic environment. Rate of caner associated cell markers on stem cells was determined by flow cytometry. Inflammatory cytokine levels in culture supernatant were determined by enzyme-linked immunoassay. The results showed that after cultured under hypoxic environment for 48 h, the cancer associated cell markers increased significantly in stem cells. IL-1beta levels increased markedly after cultured in hypoxia. Macrophages were identified as the major source of IL-1beta. Blocking IL-1beta abolished the differentiation of cancer associated cell markers in stem cells. We conclude that hypoxia can increase aberrant expression of IL-1beta in macrophages that further facilitates the expression of cancer associated cell markers in stem cells.